STUDIES ON THE TOXICOLOGICAL EFFECT OF ASULOX - 40 AND EMISAN -6 TO EGG AND EARLY LIFE HISTORY STAGES OF SAROTHERODON MOSSAMBICUS - PANDYA, S S; RAO, K S (Fishery Technology, 2017)
Toxicological effects of Asulox-40 and Emisan-6 to eggs and early life history stages of Sarotherodon mosst,;,mbicus were reported. 80% of egg hatching occurred in the controls, 1 p.p.m and 5 p.p.m concentrations of Asulox-40. 10 p.p.m. and 50 p.p.m. concentrations of the same toxicants had 70% and 60% hatchings while in Emisan-6 in the same concentrations the hatching were 70% and! 40%. Jn 100 p.p.m. concentration of both the toxicants 20% incomplete hatching occurred. In Emisan-6 Le 50 and Le 100 values were recorded at 32 hand 96 h respectively in 10 p.p.m. concentratior:s. In Asulox-40the same valuc,s were recorded in 24 hand 40 h respectively at 50 p.p.m. concentration. The fish activity during the experimental period showed initial hyper aciivity. It was established that the Emisan-6 is more harmful to S. mossambicus than Asulox-40. The harmless concentrations of these chemicals were 1.2 p.p.m. for Asulox-40 and 0.6 p.p.m. for Emisan-6.